Healing Ability of Endodontic Filling Materials in Retrograde Treatment: A Systematic Review of Clinical Studies - Tarek Ashi; Rim Bourgi; Carlos Enrique Cuevas-Suárez; Louis Hardan; Carmen Nahat; Zaher Altaqi; Naji Kharouf; Youssef Haikel (Applied Sciences)
The fundamental goal of endodontic surgery is to remove the infection cause and create an ideal environment for periapical tissue and bone recovery. This systematic review aims to present evidence-based findings regarding the healing ability of endodontic materials in retrograde treatment. The study evaluates the advantages and drawbacks of commonly utilized materials, empowering clinicians with valuable insights for preoperative planning in endodontic surgery. A comprehensive search was conducted across multiple databases, including MEDLINE, Scielo, Web of Science, Scopus, Embase, and Google Scholar, using the PIOT framework. A total of 3124 papers were identified, of which 2534 remained after removing duplicates. Following a stringent selection process, 35 clinical studies were included for qualitative assessment. The risk of bias was assessed using the Risk of Bias in Non-randomized Studies—of Interventions (ROBINS-I) tool for non-randomized trials, the Newcastle–Ottawa Scale for cohort studies, and the Joanna Briggs Institute (JBI) critical appraisal checklist for cross-sectional studies. Due to high heterogeneity in study designs and outcomes, a meta-analysis could not be performed. The review identified Super Ethoxybenzoic Acid (Super EBA), Mineral Trioxide Aggregate (MTA), and Intermediate Restorative Material (IRM®), Retroplast, Endosequence®, and gutta-percha as the primary retrograde root filling materials. Follow-up periods ranged from 6 months to 17.5 years. Although the materials showed varying degrees of success, the overall findings highlighted that no single material demonstrated universally superior healing ability. The review also emphasized the need for standardization in future clinical trials to facilitate better comparisons. The selection of retrograde filling materials plays a pivotal role in the success of endodontic surgery. New bioceramic materials like MTA and Biodentine offer improved sealing, biocompatibility, and tissue regeneration compared to traditional materials, leading to better clinical outcomes.